PEMERTALAN KARYA YUNANI SEBAGAI AWAL FILSAFAT ISLAM - Ari Jauharuddin Sanusi; Yuka Tama Mahmuda; Gazali Gazali (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
The development of Islamic philosophy is inextricably linked to the process of translation and translation (Islamization and adaptation) of Greek philosophical works into Arabic during the Abbasid Dynasty. This movement was not merely a translation, but a creative effort by Muslims to integrate Greek rationality with Islamic teachings. Through institutions such as the Bayt al-Hikmah in Baghdad, translators like Hunayn ibn Ishaq and thinkers like al-Kindi, al-Farabi, Ibn Sina, and Ibn Rushd played a crucial role in developing a new synthesis between revelation and reason. The translation of Greek works resulted in an epistemological transformation that enabled the birth of an original Islamic philosophical system, not merely an imitation but also a reinterpretation of Greek concepts of metaphysics, ethics, and logic. This process demonstrates that Islamic philosophy emerged not from passive imitation of Hellenism, but rather as the result of an intellectual dialogue between Greek tradition and Islamic monotheistic values. Thus, the translation of Greek works laid the foundation for the formation of a rational, theological, and universal mode of philosophical thought in Islamic civilization